ANALISI PEMBANGUNAN KONSERVASI SUMBER DAYA AIR OLEH BADAN LINGKUNGAN HIDUP DI KOTA PEKANBARU (Studi Kasus Anak Sungai Siak) - Yuliani Pramita; Tuti Khairani Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Administration building is indispensable in making a country's development it is veryimportant for the State IndonesiaDevelopment issues of water resources conservation by environmental agency in Pekanbaru City case study tributary siak very difficult to find a solution to stop the pollution in every tributary siak that by comparing the domestic waste and environmental agency to reduce contamination of creens siak environmental agency management of the program times net (PROKASIH) one program intended to improve the water quality of the river so that meets its functions.To analyze these problems the author uses the theory of Thompson, which corresponds to these problems the administration building is the organization's ability to "innovate" (resource upgrade) orientation of this approach is a change in the future a better and promising. The orientation towards change and upgrade means showing action-oriented development administration - real activities in achieving objectives. In making changes and upgrade in the future must be balanced with real involvement activities in the present as a springboard to achieve better success in the future.This research is a descriptive qualitative approach, data collection techniques are observation, interviews, documentation and interviews with key informants as a key resource.These results indicate that not maximal implementation of development conservation of water resources by the environmental agency contamination of creeks siak carried out by the environmental agency in this case looks much pollution as a result of the domestic diposal waste are carried out by people who live in the watershed tributary siak.Keywords: Administrative Development, Pollution Environmental, Conservation Of Water Resources